History and prospects of artificial intelligence - Abdujabborov Madaminjon (Zien Journals, 2023)
This article explores the history and development of artificial intelligence (AI) from ancient times to the present day. It discusses the opportunities presented by AI and highlights the normative documents related to the development of artificial intelligence in Uzbekistan
Keywords: Artificial intelligence; computer; robot; cognition